2020
DOI: 10.1021/jacs.0c06916
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Dipyrromethenes: Bright Cationic Fluorescent Dyes and Potential Application in Revealing Cellular Trafficking of Mitochondrial Glutathione Conjugates

Abstract: Boron−dipyrromethenes (Bodipys), since first reported in 1968, have emerged as a fascinating class of dyes in the past few decades due to their excellent photophysical properties including bright fluorescence, narrow emission bandwidth, resistance to photobleaching, and environment insensitivity. However, typical Bodipys are highly lipophilic, which often results in nonfluorescent aggregates in aqueous solution and also severely limits their bioavailability to cells and tissues. In this work, based on a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 68 publications
1
31
0
1
Order By: Relevance
“…44), 156,159,[162][163][164][165] rigidification of the conjugated backbone by annelation, 166 167 or replacement the boron centre by a carbon atom, in recently disclosed cardipy dyes. 168 According to theoretical predictions, the combination of these approaches would lead to highly red-shifted absorptions, up to ca. 1000 nm for the most optimized structures.…”
Section: Polymethine Approachmentioning
confidence: 99%
“…44), 156,159,[162][163][164][165] rigidification of the conjugated backbone by annelation, 166 167 or replacement the boron centre by a carbon atom, in recently disclosed cardipy dyes. 168 According to theoretical predictions, the combination of these approaches would lead to highly red-shifted absorptions, up to ca. 1000 nm for the most optimized structures.…”
Section: Polymethine Approachmentioning
confidence: 99%
“…Organic fluorophores are widely used in many areas such as fluorescent probes [1][2][3][4][5][6] , bioimaging [7][8][9][10][11] and organic light emitting diodes [12][13][14] . Normally, exciting a fluorophore in dilute solution generates a lowest singlet excited state (S 1 ), which rapidly relaxes back to the ground state (S 0 ) through emitting fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the images that most of the NP's surrounded the cell nuclei, which suggest cytoplasmic localization. [ 37,38 ] Additionally, these findings revealed that the NPReL induced the changes broadly in cytoplasmic skeleton and nuclei, therefore causes the cytotoxicity to the c6 cancer cells. Furthermore, quantified uptake or association of NPReL with cells and the accurate quantification of rhenium content was analyzed by ICP‐MS.…”
Section: Resultsmentioning
confidence: 89%